Prevalence of traded bird species in key biodiversity areas - Oscar Morton; Tom Lansley; Stuart H. M. Butchart; Graeme M. Buchanan; David P. Edwards (Conservation Biology, 2026)
The use and trade of biodiversity involve tens of thousands of species that are exploited at a range of scales, intensities, and degrees of sustainability. As a result, some are highly threatened. Key biodiversity areas (KBAs) are sites of significance for the persistence of biodiversity identified nationally based on standardized criteria. The degree to which biodiversity in KBAs is likely to be used and traded is not well understood. We undertook a fine‐scale assessment of the area of habitat (AOH) of traded species in KBAs. We used data on >16,000 KBAs and combined these with AOH maps for >10,000 bird species, a heavily traded and well‐documented indicator taxon. We subsequently mapped and quantified the distribution of traded species richness, extinction risk, and range‐size rarity in and adjacent to KBAs. Although less than half of all bird species are traded, we found that most bird species in KBAs were traded, and the richness of traded species was more than twice (119%) that of nontraded species. Traded species had comparable proportions of their AOH (22.5% on average) in KBAs as nontraded species (21.5%). Global hotspots of richness, extinction risk, and range rarity for traded species disproportionately occurred in KBAs, which had higher levels of extinction risk and range rarity for traded species than locations immediately outside KBAs. Of the 46 species that are likely threatened by unsustainable use and have the majority of their habitat falling within KBAs, we found that eight species had no habitat in designated protected areas. Reconciling sustainable use and the critical importance of KBAs for threatened species is essential. Our results suggest that for some species, there is an urgent need to protect key sites and ensure that any use and trade of species within them are sustainable.